2011
DOI: 10.1007/s00586-011-2050-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of and patient satisfaction with cervical laminoplasty for considerable cord compression with only slight myelopathy

Abstract: Purpose There is no established consensus on the indications for surgery in patients with considerable cord compression but only slight myelopathy. The purpose of this study is to stimulate discussion about the indications for surgery in these patients. Methods The records of consecutive patients who underwent cervical laminoplasty (CLP) during 3.5 years were reviewed. Those patients whose pre-operative Japanese Orthopaedic Association score (JOA score, maximum 17) for cervical myelopathy was 16 points or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…This was favorable compared to the responses of dissatisfied patients who had a mean postoperative score of 8.53, lower than that (0.47) at baseline. This relationship has been reported in several other studies that demonstrate either a correlation between an absolute lower score on the VAS, Numerical Rating Scale, or other pain scale and higher satisfaction rates [14,29,40] or, more commonly, a decrease in the postoperative pain a higher rate of satisfaction [16,17,19,22,25,38,39,41]. However, some reports show higher scores on the VAS or a similar pain scale that correlate to a lower satisfaction rate [10,24,26,28,34,37,42] or lack of pain reduction leading to lower satisfaction [25].…”
Section: Dimensions Of Patient Satisfactionsupporting
confidence: 78%
See 2 more Smart Citations
“…This was favorable compared to the responses of dissatisfied patients who had a mean postoperative score of 8.53, lower than that (0.47) at baseline. This relationship has been reported in several other studies that demonstrate either a correlation between an absolute lower score on the VAS, Numerical Rating Scale, or other pain scale and higher satisfaction rates [14,29,40] or, more commonly, a decrease in the postoperative pain a higher rate of satisfaction [16,17,19,22,25,38,39,41]. However, some reports show higher scores on the VAS or a similar pain scale that correlate to a lower satisfaction rate [10,24,26,28,34,37,42] or lack of pain reduction leading to lower satisfaction [25].…”
Section: Dimensions Of Patient Satisfactionsupporting
confidence: 78%
“…Improvement in functional capacity naturally has a positive effect on satisfaction; this association is also reported in the literature; 30 of the studies we reviewed reported that measurement of the functional outcome is a controlling factor in overall patient satisfaction [6,10,13-18,20,21,23,26-29,34-37,39,40,43-51]. The most common outcome measures reported were the SF-36 Physical Component Summary, the Oswestry Disability Index (ODI), and various iterations of the Scoliosis Research Society questionnaire.…”
Section: Dimensions Of Patient Satisfactionsupporting
confidence: 67%
See 1 more Smart Citation
“…Cervical laminoplasty is a well-established treatment for myelopathies with relatively good results in terms of improving neurological findings [1] and symptoms and a high degree of satisfaction even in cases of relatively mild preoperative myelopathy [2] . To the best of our knowledge, most previous studies have included multiple diseases such as ossification of the posterior longitudinal ligament (OPLL) and cervical disk herniation (CDH), and there are a few studies investigating postoperative satisfaction and patient-reported outcomes (PROs) in patients with cervical spondylotic myelopathy (CSM) alone [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, postoperative axial neck pain has been reported as a complication after cervical laminoplasty. 3-9 Because postoperative axial pain will affect a patient’s satisfaction and health-related quality of life, 10-12 surgeons should consider the preoperative risk factors and anticipate this surgery-related complication.…”
Section: Introductionmentioning
confidence: 99%